Collider signatures of coannihilating dark matter in light of the B-physics anomalies - Michael J. Baker (SpringerOpen, 2021)
Abstract Motivated by UV explanations of the B-physics anomalies, we study a dark sector containing a Majorana dark matter candidate and a coloured coannihilation partner, connected to the Standard Model predominantly via a U 1 vector leptoquark. A TeV scale U 1 leptoquark, which couples mostly to third generation fermions, is the only successful single-mediator description of the B-physics anomalies. After calculating the dark matter relic surface, we focus on the most promising experimental avenue: LHC searches for the coloured coannihilation partner. We find that the coloured partner hadronizes and forms meson-like bound states leading to resonant signatures at colliders reminiscent of the quarkonia decay modes in the Standard Model. By recasting existing dilepton and monojet searches we exclude coannihilation partner masses less than 280 GeV and 400 GeV, respectively. Since other existing collider searches do not significantly probe the parameter space, we propose a new dedicated search strategy for pair production of the coloured partner decaying into bbττ final states and dark matter particles. This search is expected to probe the model up to dark matter masses around 600 GeV with current luminosity.